The Cellular Transcriptome in the Maternal Circulation During Normal Pregnancy: A Longitudinal Study - Gomez-Lopez, Nardhy; Romero, Roberto; Hassan, Sonia S.; Bhatti, Gaurav; Berry, Stanley M.; Kusanovic, Juan Pedro; Pacora, Percy; Tarca, Adi L. (Frontiers in Immunology, 2019)
Pregnancy represents a unique immunological state in which the mother adapts to tolerate the semi-allogenic conceptus; yet, the cellular dynamics in the maternal circulation are poorly understood. Using exon-level expression profiling of up to six longitudinal whole blood samples from 49 pregnant women, we undertook a systems biology analysis of the cellular transcriptome dynamics and its correlation with the plasma proteome. We found that: 1) chromosome 14 was the most enriched in transcripts differentially expressed throughout normal pregnancy; 2) the strongest expression changes followed three distinct longitudinal patterns, with genes related to host immune response (e.g. MMP8, DEFA1B, DEFA4, LTF) showing a steady increase in expression from 10 to 40 weeks of gestation; 3) multiple biological processes and pathways related to immunity and inflammation were modulated during gestation; 4) genes changing with gestation were among those specific to T cells, B cells, CD71+ erythroid cells, natural killer cells, and endothelial cells, as defined based on the GNF Gene Expression Atlas; 5) the average expression of mRNA signatures of T cells, B cells, and erythroid cells followed unique patterns during gestation; 6) the correlation between mRNA and protein abundance was higher for mRNAs that were differentially expressed throughout gestation than for those that were not, and significant mRNA-protein correlations were observed for genes part of the T-cell signature. In summary, unique changes in immune-related genes were discovered by longitudinally assessing the cellular transcriptome in the maternal circulation throughout normal pregnancy, and positive correlations were noted between the cellular transcriptome and plasma proteome for specific genes. These findings provide insights into the immunobiology of normal pregnancy.